Influence of leaf age, soil moisture, VPD and time of day on leaf conductance of various Musa genotypes in a Humid Forest Moist Savanna transition site - Ekanayake, I.J.; Ortíz, R.; Vuylsteke, D.R. (Oxford University Press, 1994)
Leaf age effects on the leaf conductance to water vapour diffusion of the adaxial and abaxial leaf surfaces were measured in the morning and in the afternoon on 17 different plantain and banana (Musa spp.) genotypes. The irradiance levels increased three-fold while leaf to air vapour pressure deficit levels increased two- to four-fold from morning to afternoon during the sampling period in a field site located in the humid forest-moist savanna transition zone of Nigeria. Conductance values were reduced in older, and senescing leaves relative to the young and mature leaves both in the morning and in the afternoon. Conductances were higher for the abaxial leaf surfaces than the adaxial surface and higher in the afternoon than in the morning, with some genotypic differences. Lower values of leaf conductance to water vapour in the afternoon under a short dry spell was sufficiently variable (P ⩾ 0•05) among the test genotypes to indicate potential adaptation to transient dry conditions. Differential and relative leaf conductance adjustments were noted among genotypes experiencing a short dry spell versus non-limiting soil moisture conditions. Significant genotypic differences were observed for leaf conductance among the 17 genotypes during the afternoon on the lower leaf surface of younger leaves. ABB cooking banana cultivars 'Fougamou' and 'Bluggoe' might be potentially promising cultivars for transient dry conditions while AAB plantain 'Bobby Tannap' and one of its hybrids TMPx 582-4 could be very sensitive to short dry spells according to this evaluation.